Comparison of antioxidant activity of extract of Green tea to commercial antioxidants in 2% hydroquinone cream - K Morteza-Semnani; M Saeedi; Z Nozadi (Institue of Medicinal Plants, ACECR, 2005)
Background: Recently, many researchers have been involved in finding means to prevent or delay deterioration by oxidative reactions in cosmetic preparations. More recently, research has focused on developing safer and more effective antioxidants from natural sources. Objective: In this research the antioxidant activity of Green tea extract in comparison with commercial antioxidants in 2% hydroquinone cream were evaluated. Method: Green tea extract was tested for antioxidative activity in comparison with antioxidants (sodium metabisulfite and butilated hydroxy toluene BHT) at 0.1%, 0.5%, 1.0% and 2.0% w/w in 2% w/w hydroquinone cream. The systems were incubated in a dark room at 25°± 0.5°C and 45°± 0.5°C for three months. The physical stability and the percentages of hydroquinone remaining after two weeks and one, two, and three months were determined. Results: The experiment revealed that oxidation degradation of hydroquinone was accelerated by heat even with existence of antioxidants. In the third month at 25°± 0.5°C and 45°± 0.5°C, the extract demonstrated more antioxidant activity from other two commercial antioxidants at all concentrations, with about 43-53% and 32-44%, respectively, more hydroquinone remaining than in the control system (P<0.001). In the third month, the preparation containing 0.1%, 0.5%, 1.0% and 2.0% extract gave good physical formulation stability with about 70%, 75%, 77% and 81% hydroquinone remaining at 25°± 0.5°C, and 50%, 54%, 58% and 62% hydroquinone remaining at 45°±0.5°C, respectively. Conclusion: This suggested the possibility of using a Green tea extract as an effective natural antioxidant for substances that are oxidation-susceptible.